Linking Upper‐Plate Fault Reactivation With the Megathrust Earthquake Cycle: The Case of the Northern Chile Outer Forearc (19°S–23°S). Issue 11 (4th November 2022) - Cortés‐Aranda, J.; González, J.; Molina, D.; Astudillo‐Sotomayor, L.; Tassara, A.; Miller, M.; Álvarez‐Amado, F.; González, R.; Bahamondes, D.
Abstract: Crustal faults above subduction megathrusts have been shown to have the capacity to produce moderate‐to‐large earthquakes (fault reactivation), causing severe damage for inhabited areas in the vicinity. Fault reactivation has been dynamically related to the interseismic stage of the subduction cycle and to megathrust earthquakes. In the northern Chile outer forearc (19°S–23°S), published works have demonstrated that six faults of different orientation and kinematics produced M  ∼ 7 paleoearthquakes during the Late Quaternary; these lie above the interplate rupture of the 1877 M8.7 Iquique Earthquake. Here, we assess the potential of these and similar faults to experience reactivation due to stress perturbations induced by the interseismic and coseismic phases of the megathrust earthquake cycle. To do so, we compute Coulomb Failure Stress changes (ΔCFS) produced by different megathrust locking/earthquakes (real and synthetic) scenarios. Our results show that fault reactivation is enhanced by both interseismic and coseismic stages. Furthermore, they suggest that reverse slip on EW and NS faults is favored during the interseismic stage; in turn, faults of different orientations and kinematics are favored following megathrust earthquakes. The easiest way to promote the reactivation of most of the considered faults is with interplate ruptures slipping within (but not necessarily restricted to) the seismogenic zone between 20°S and 23°S. These ruptures would augment the hazard from crustal faulting in the area. These results highlight the need to continue studying the paleoseismology of these faults and their dynamic link with the megathrust seismic cycle, in this and other subduction margins. Plain Language Summary: Although smaller and less recurrent than earthquakes occurring on the interplate contact of subduction margins, seismic events on crustal faults (fault reactivation) may cause severe damage for inhabited areas in the vicinity. Former studies suggest that fault reactivation may occur during the interseismic phase (the time period between two successive earthquakes) of the subduction cycle or following megathrust earthquakes. This is, both phases may induce stress perturbations on crustal faults and, eventually, produce their reactivation. Herein, we calculate the stress perturbations induced by interseismic and coseismic scenarios on seismogenic crustal faults in the northern Chile outer forearc (19°S–23°S). These faults occur directly above a subduction segment that contained the great 1877 Iquique Earthquake. Our results suggest that both interseismic and coseismic stages of the megathrust cycle may produce fault reactivation; nevertheless, each stage favors specific fault types. Furthermore, our results indicate that a great megathrust earthquake in the area could promote the reactivation of most of the upper crustal faults, increasing the seismic hazard in the region. This study is relevant when considering the interaction between interplate processes and crustal fault reactivation to better assess the seismic hazard in this and other subduction zones. Key Points: Coulomb stress changes show that fault reactivation in the area may be caused by interseismic/coseismic stages of the subduction cycle Reverse slip on NNW to NE faults may occur in the interseismic stage; faults of different kinematics and orientations may slip coseismically The easiest way to reactivate most of these faults is with ruptures slipping the interplate zone between 20°S and 23°S